Neutrino physics: experimental and theoretical challenge - Gonzalez Felipe, Ricardo (2023)
The existence of massive neutrinos is the first solid evidence of physics beyond the standard model of particle physics. A remarkable progress has been achieved in solar, atmospheric, reactor, and accelerator neutrino experiments during the last decades. On the theoretical side, several questions are being addressed, namely the Dirac or Majorana nature of neutrinos, the mechanisms for neutrino mass generation, and the relation between neutrinos and the matter-antimatter asymmetry observed in the Universe, among others. This article provides a brief overview on some of the current experimental and theoretical aspects in neutrino physics.